Desa Tehang Teknologi Tepat Guna E-Government Kotim Untuk Kependudukan dan Administrasi Umum Studi Kasus Desa Tehang - Mirendi Mirendi; Depi Rusda (Journal of Computer System and Informatics (JoSYC), 2020)
Tehang Village is one of the villages located in Parenggean District. The delivery of population data collection information and certificate services provided is still not ineffective and efficient, because the information and certificate services received by the public and also to the general public are still not computerized. This is because when the village community is interested and in general viewing village information, they must come to the tehang village office to view village information. When the people of Tehang Village submitted a certificate, and the data for the population who submitted the certificate was still stored in computer documents and had not been saved to the system. The obstacle that often arises when residents submit another letter is a letter, a letter stored by an infected virus so that it affects the service to the people of Tehang Village. Therefore, the system that will make researchers is an E-government system in Tehang Village which is used to provide certificate services, making certificates, incoming letters, outgoing letters and Village information to the people of Tehang Village which can be accessed by the people of Tehang Village, or general public